Analisis Bibliometrik Muslimah Berkarier pada Database Dimensions - Alya Huriah Assegaff (Gunung Djati Conference Series, 2023)
This study of career Muslim women explains the participation of women in the world of work or those whose sphere of influence is in the public sector, but it also raises several provocative questions about the role of women as internal person in charge of the family. So this issue is debated among Muslim academics. In addition, the purpose of this research is to collect and analyze existing data related to these career Muslim women. The method used is bibliometric analysis with database dimensions on the keyword ''career Muslim women'' in 84 articles. By using this database, data can be found that can be analyzed in several categories, namely research categories, publication developments, researchers and places of publication related to research on Muslim women with careers. The results obtained after conducting this research are that the highest research category is found, namely in the study category in society. This research develops every year so that the highest research is found in 2019, although this research needs to be increased again by researchers, related to researchers tend to be evenly distributed and the place of publication that publishes the most, namely the journal Marwah Jurnal Perempuan. It should be noted that it is important to study career Muslim women in order to know what professions should be like for women in Islam or so on. Thus this study needs to be further developed and maintained.